Modification of soil structure of sand tailings: I. preliminary study on the effect of organic amendment and iron on soil aggregation - A. M., Mokhtarudin; M., Norhayati (Universiti Pertanian Malaysia Press, 1995)
The effectiveness of dried palm oil mill effluent (decanter cake), which contains 14% organic carbon, and iron solution in promoting aggregation in sand tailing soil was determined. The addition of iron (JT decanter cake at rates of 20 and 60 t h«l had no significant effect on the aggregation and stability of the sand. At a higher rate of 100 t h«l, decanter cake gave a significant effect on aggregate stability. With the addition of 0.1 % Fe, the rate of decanter cake application for effective stabilization was reduced to almost half. However, generally the extent of aggregatian was law (% aggregation>2mm was only 5.6%). This could be due to the low amount of very fine sand and silt amounting to only 5.8%, and the absence of clay in the sand tailings. It is postulated that an improvement in the soil structure of sandy tailings using amendments essentially requires the presence of fine soil fractions viz. clay and silt and/or very fine sand in sufficient amounts. Their presence will kad to better soil structure Jonnation in the sand tailings by the amendments and hence to better water and nutrient economy of the soil.